Effects of Service Quality on Customer Satisfaction in Life Insurance Companies in Karnali Province, Nepal - Shahi, Dilip Jung (Journal of Nepalese Management and Research, 2025)
In life insurance, customer satisfaction depends largely on service quality, as trust, reliability, and the quality of interactions often matter more than the tangible product itself. The SERVQUAL dimensions, i.e., tangibility, reliability, responsiveness, assurance, and empathy, play a key role in shaping customer perceptions. While studies in Nepal highlight the importance of responsiveness, assurance, and empathy, research in remote regions remains limited. Karnali Province, with its low financial literacy and restricted access to services, presents a unique context for studying these dynamics. This study investigates how the five SERVQUAL dimensions affect customer satisfaction in life insurance companies operating in Karnali Province and identifies the most influential factors to guide service improvements. A descriptive and causal-comparative design was adopted. Primary data were collected from 150 customers through a structured questionnaire out of 200 distributed. Reliability testing, correlation analysis, and multiple regression were applied using SPSS to examine the impact of each service quality dimension on satisfaction. The analysis shows that empathy was the strongest driver of customer satisfaction, followed by tangible service elements and staff assurance. Reliability had minimal impact, while responsiveness unexpectedly demonstrated a negative relationship with satisfaction. These findings suggest that emotional connection and understanding matter more to customers than operational efficiency alone. The findings suggest the importance of personalized attention, professional competence, and well-maintained facilities in enhancing satisfaction. They also indicate that the influence of service quality dimensions varies across regions, offering practical guidance for improving insurance services in underserved areas.